Air Filtration Technology in Reducing the Risk of Health Problems Society: A Review - Ardiati, Siti; Fadila, Nur; Rahmadani, Suci (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Air quality is a fundamental determinant of human health, particularly affecting respiratory and cardiovascular systems. Rapid industrialization, urbanization, and increased transportation have significantly elevated air pollution levels worldwide. The World Health Organization (WHO, 2020) reports that approximately 99% of the global population is exposed to air quality below recommended safety standards. Similarly, the Ministry of Environment and Forestry (2023) indicates that major cities in Indonesia continue to experience unhealthy air quality indices. Exposure to pollutants such as fine particulate matter (PM ₂.₅ and PM₁₀), oxidative gases, and airborne microorganisms is associated with chronic respiratory diseases, asthma, and cardiovascular disorders. Consequently, effective mitigation strategies are required to minimize the adverse health impacts of air pollution. Objectives: This study employs a Systematic Literature Review (SLR) approach to evaluate the effectiveness of modern air filtration technologies in reducing health risks associated with air pollution. Methods: The study follows PRISMA guidelines, analyzing more than 20 national and international journal articles published between 2019 and 2025. Data were collected from Google Scholar, ScienceDirect, and PubMed using keywords including air filtration technology, HEPA filter, nanofiber filter, and IoT-based air purifier. Results: Findings indicate that HEPA filters, UV-C sterilization, PVDF and PU nanofibers, and IoT-based systems achieve filtration efficiencies up to 99.9%. Combined HEPA and UV-C effectively inactivate SARS-CoV-2, while nanofiber filters enhanced with MoS₂ and CuO nanoparticles exhibit additional antimicrobial properties. Conclusion: Air filtration technologies offer an effective and sustainable solution for improving air quality and reducing public health risks. Keywords: Air pollution; Air filtration technology; HEPA filter; UV-C; Nanofiber; IoT-based air purifier; Public health.